Terrace wear-resistant layer mortar based on high-titanium blast furnace slag and preparation method thereof

By preparing the floor wear-resistant layer mortar based on high-titanium blast furnace slag, the problem of failure to effectively utilize the high-titanium blast furnace slag is solved, and its efficient use in the floor field is achieved, which improves its compression, flexural and wear resistance. performance, reducing environmental pollution.

CN119430792AActive Publication Date: 2025-02-14HENAN LIANYANG NEW ENVIRONMENTALLY FRIENDLY BUILDING MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411445108.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-14
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The high-titanium blast furnace slag has not been effectively utilized in the prior art, resulting in direct dumping and accumulation, seriously threatening environmental safety. At the same time, its gelling activity is low and it is difficult to directly use as cement mixed materials and blends.

Method used

By preparing a floor wear-resistant layer mortar based on high-titanium blast furnace slag, the raw materials include cement, silicon powder, high-titanium blast furnace slag, water reducing agent and water, the mass ratio of cement to high-titanium blast furnace slag is (35~45) :(55-65), the water-cement ratio is 0.20-0.28, and the amount of water-reducing agent is 0.06-0.12% of the total mass of cement and high-titanium blast furnace slag.

Benefits of technology

The simple and efficient use of high-titanium blast furnace slag is achieved. The prepared floor wear-resistant layer mortar has flexural resistance, high compressive strength, high wear resistance ratio, and small surface average indentation diameter, which solves the accumulation of high-titanium blast furnace slag Environmental issues have improved their application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430792A_ABST
    Figure CN119430792A_ABST
Patent Text Reader

Abstract

The invention discloses floor wear-resistant layer mortar based on high-titanium blast furnace slag and a preparation method thereof, and belongs to the technical field of comprehensive development and utilization of industrial solid wastes. The floor wear-resistant layer mortar based on the high-titanium blast furnace slag is prepared from the following raw materials: cement, silicon powder, the high-titanium blast furnace slag, a water reducing agent and water, the mass ratio of the cement to the high titanium blast furnace slag is (35-45): (55-65). The high-titanium blast furnace slag is used for preparing the floor wear-resistant layer mortar which is high in fracture resistance and compressive strength, high in wear resistance ratio and small in surface average indentation diameter.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of comprehensive development and utilization of industrial solid waste, and in particular to a floor wear-resistant layer mortar based on high-titanium blast furnace slag and a preparation method thereof. Background Art

[0002] High-titanium blast furnace slag is the molten slag produced when smelting pig iron with vanadium-titanium magnetite as raw material. At present, the actual utilization rate of high-titanium blast furnace slag is low, and most of the high-titanium blast furnace slag is directly dumped and piled up in the slag yard, which seriously threatens environmental safety. Many scholars have conducted a lot of research on the resource utilization of high-titanium blast furnace slag and achieved certain results, among which the resource utilization of high-titanium blast furnace slag building materials is the focus of research.

[0003] At present, the utilization of high-titanium blast furnace slag as building materials is mainly concentrated in the use as cementitious materials, concrete aggregates, functional building materials, etc. However, the cementitious activity of high-titanium blast furnace slag is low, and it does not have the application potential to be directly used as cement mixed materials and admixtures. It is necessary to use mechanical and chemical activation, compounding with active admixtures, etc. to improve its cementitious properties. It is generally used as an auxiliary cementitious material or to make multi-component composite cementitious materials. High-titanium blast furnace slag is used as concrete aggregate, and its performance is better than that of natural aggregate concrete. It can be used to prepare ultra-high performance concrete with a grade exceeding C120, but there are problems with irregular morphology and large pores, which will cause high-performance concrete to begin to break along the aggregate. In terms of functional building materials, it is mainly concentrated on the use of high-titanium blast furnace slag to prepare microcrystalline glass and cast stone, sanitary porcelain panels and ceramic tiles.

[0004] At present, there are no reports on the use of high-titanium blast furnace slag (the floor industry has relatively mature wear-resistant products, and high-titanium blast furnace slag is generally only used as aggregate) to prepare cement-based floor surface mortar. Summary of the invention

[0005] The purpose of the present invention is to provide a floor wear-resistant layer mortar based on high-titanium blast furnace slag and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] One of the technical solutions of the present invention: a floor wear-resistant layer mortar based on high-titanium blast furnace slag, the raw materials of which include cement, silica fume, high-titanium blast furnace slag, water reducing agent and water;

[0008] The mass ratio of the cement to the high-titanium blast furnace slag is (35-45):(55-65).

[0009] Furthermore, the water-cement ratio of the floor wear-resistant layer mortar is 0.20 to 0.28;

[0010] The dosage of the water reducing agent is 0.06-0.12% of the total mass of cement and high-titanium blast furnace slag.

[0011] Furthermore, the floor wear-resistant layer mortar includes the following raw materials in parts by mass: 770 parts of cement, 22 parts of silicon powder, 1430 parts of high-titanium blast furnace slag, 221.80 parts of water and 2.64 parts of water reducing agent.

[0012] Furthermore, the particle size of the high-titanium blast furnace slag is 10 to 70 meshes.

[0013] Furthermore, the content of TiO2 in the high-titanium blast furnace slag is 20-28%.

[0014] The chemical composition and physical properties of high-titanium blast furnace slag have a decisive influence on its performance as a floor wear-resistant layer mortar. The content of titanium in high-titanium blast furnace slag directly determines its hardness and wear resistance, while other metal oxides and silicates in the slag have an important influence on its corrosion resistance, stability and other properties. When the content of TiO2 in high-titanium blast furnace slag is 20-28%, a floor wear-resistant layer mortar with high hardness, good wear resistance, corrosion resistance and stability can be obtained.

[0015] The particle size of high-titanium blast furnace slag (aggregate) and the gradation ratio of aggregates of different particle sizes have an important influence on the wear resistance of the floor. Aggregates with appropriate particle size can better combine with the floor substrate to form a stable wear-resistant layer, and reasonable particle size and gradation affect the flatness and density of the floor surface. When the particle size of 17-2.36mm accounts for 5%, the particle size of 1.18-1.7mm accounts for 40%, the particle size of 0.6-1.18mm accounts for 35%, the particle size of 0.3-0.6mm accounts for 17%, and the particle size of 0.21-0.3mm accounts for 3%, a floor wear-resistant layer mortar with good wear resistance, high flatness and density can be obtained.

[0016] The second technical solution of the present invention is a method for preparing the above-mentioned floor wear-resistant layer mortar, comprising the following steps:

[0017] The raw materials are mixed evenly to obtain the floor wear-resistant layer mortar.

[0018] The third technical solution of the present invention: an application of the above-mentioned floor wear-resistant layer mortar as a floor material.

[0019] The present invention discloses the following technical effects:

[0020] The present invention uses high-titanium blast furnace slag to prepare a floor wear-resistant layer mortar with high flexural and compressive strength, high wear resistance ratio and small average surface indentation diameter.

[0021] The invention can realize the simple and efficient utilization of high-titanium blast furnace slag, and solves the problem that high-titanium blast furnace slag is directly dumped and accumulated in a slag yard, which seriously threatens environmental safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 The figure is a test diagram of the fluidity of the mortar of the present invention, as well as a physical diagram of the mortar specimen, the standard curing control equipment, and the HYE-300B microcomputer electro-hydraulic servo pressure testing machine;

[0024] Figure 2 This is the wear resistance test process of the mortar specimen of the present invention;

[0025] Figure 3 This is a surface strength testing process of the mortar specimen of the present invention;

[0026] Figure 4 This is a physical picture of the unscreened high-titanium blast furnace slag used in the present invention. DETAILED DESCRIPTION

[0027] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0028] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0029] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0030] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0031] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0032] The “parts” described in the following examples are all “parts by mass”.

[0033] The raw materials used in the present invention are as follows:

[0034] (1) Cement

[0035] Cement (ordinary Portland cement) was provided by Sichuan Esheng Cement Co., Ltd., with a strength grade of 42.5R. The technical performance indicators are shown in Table 1.

[0036] Table 1 Technical performance indicators of cement

[0037]

[0038] (2) High titanium blast furnace slag

[0039] The high-titanium blast furnace slag used in the embodiment is provided by Panzhihua Steel City Group Co., Ltd. (Panzhihua Environmental Metallurgical Slag Development Co., Ltd.). The slag is slowly cooled by water beating, has few impurities, high stable mineral content, and hard texture. After screening, the particle size is between 10 and 70 meshes. Its composition is shown in Table 2.

[0040] Table 2 Composition of high titanium blast furnace slag

[0041] project <![CDATA[Na2O]]> MgO <![CDATA[Al2O3]]> <![CDATA[K2O]]> CaO <![CDATA[TiO2]]> MnO <![CDATA[SiO2]]> <![CDATA[Cr2O3]]> Impurities Content wt% 1.03 8.68 10.30 0.60 31.57 27.38 0.98 18.37 0.08 1.01

[0042] Table 3 Grading table of high titanium blast furnace slag

[0043] Particle size (mm) 1.7~2.36 1.18~1.7 0.6~1.18 0.3~0.6 0.21~0.3 Screening mesh number 10 mesh 16 mesh 30 mesh 50 mesh 70 mesh Screening percentage (%) 5 40 35 17 3

[0044] (3) Silica fume

[0045] Silica fume (microsilica powder A2) was provided by Chengdu Hengruiyuan Environmental Protection Materials Co., Ltd. The chemical composition is shown in Table 4.

[0046] Table 4 Chemical composition of silica fume

[0047] Ingredient name LOSS <![CDATA[Al2O3]]> <![CDATA[SiO2]]> <![CDATA[Fe2O3]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> <![CDATA[TiO2]]> Impurities Content wt% 1.08 0.26 96.50 0.06 0.55 0.42 0.44 0.26 0.02 0.41

[0048] (4) Water reducing agent

[0049] The water reducer (polycarboxylic acid high-performance water reducer) was provided by Jiangsu Zhaojia Building Materials Technology Co., Ltd. The water reduction rate was 26%. The technical performance indicators of the water reducer are shown in Table 5.

[0050] Table 5 Technical performance indicators of water reducer

[0051]

[0052] The water used is tap water.

[0053] Example 1

[0054] A method for preparing floor wear-resistant layer mortar based on high-titanium blast furnace slag:

[0055] According to the ratio in Table 5, cement, silica powder, high titanium blast furnace slag and water reducer were mixed evenly, and then water was added and mixed evenly to obtain 5 different floor wear-resistant layer mortars, which were recorded as A1, A2, A3, A4 and A5.

[0056] According to GB / T17671-2021, the fluidity of different floor wear-resistant layer mortars is measured using the NLD-3 cement mortar fluidity tester (see the fluidity test diagram for details). Figure 1 ), the results are shown in Table 6.

[0057] Table 6 Raw material mix ratio of floor wear-resistant layer mortar

[0058] Test piece Water-cement ratio Cement / g Silica powder / g High titanium blast furnace slag / g Water / g Water reducing agent / g Fluidity / mm A1 0.20 770 22 1430 160.6 1.76 Stir dry hair A2 0.23 770 22 1430 182.2 2.20 Too small A3 0.25 770 22 1430 198 2.20 112 A4 0.28 770 22 1430 221.8 2.42 115 A5 0.28 770 22 1430 221.8 2.64 124

[0059] The standard "Cement-based wear-resistant materials for concrete floors JCT906-2002" stipulates that the amount of water used in mortar should be determined based on fluidity, and the amount of water should make the fluidity of the mixture D = 120mm ± 5mm, so the raw material mix ratio of A5 is the most appropriate.

[0060] Effect Example 1

[0061] According to GB / T17671-2021 "Test Method for Cement Mortar Strength (ISO Method)", the compressive and flexural strength of the floor wear-resistant layer mortar is measured. The experimental equipment is HYE-300B microcomputer electro-hydraulic servo pressure testing machine;

[0062] The wear resistance ratio of the floor wear-resistant layer mortar is measured according to GB / T16925-1997 "Test method for wear resistance of concrete and its products (ball bearing method)". The experimental equipment is the ball bearing wear test machine NS-2;

[0063] The surface strength (indentation diameter, mm) of the floor wear-resistant layer mortar is determined according to GB231-1984 "Metal Brinell Hardness Test Method". The experimental equipment is a microcomputer-controlled electronic universal testing machine with a maximum load of 5KG.

[0064] The prepared floor wear-resistant layer mortar specimens should meet the Type I technical index requirements specified in the standard "Cement-based wear-resistant materials for concrete floors JCT906-2002". The technical requirements are shown in Table 7.

[0065] Table 7 Technical requirements for Type I of cement-based wear-resistant materials for concrete floors JCT906-2002

[0066]

[0067]

[0068] Among them, "approximately" means that the color difference is basically invisible to the naked eye, and "slightly" means that there seems to be a little color difference to the naked eye.

[0069] (1) Flexural and compressive strength

[0070] The floor wear-resistant layer mortar (A5) prepared in Example 1 was made into a standard mortar specimen using a 40mm×40mm×160mm triple mold. After standard curing for 7d and 28d, the flexural and compressive strengths were measured (the actual pictures of the mortar specimen, standard curing control equipment, and HYE-300B microcomputer electro-hydraulic servo pressure testing machine are shown in Figure 1 ), the results are shown in Table 8.

[0071] Table 8 Flexural and compressive strength of floor wear-resistant layer mortar specimens

[0072] project Flexural strength / 7d, MPa Compressive strength / 7d, MPa Flexural strength / 28d, MPa Compressive strength / 28d, MPa Test data 12.6 91.2 14.8 110.3 Standard requirements / / 11.5 80

[0073] It can be seen from Table 8 that the initial strength of the floor wear-resistant layer mortar specimens is good, and the flexural and compressive strengths increase with the increase of curing time. Compared with the standard requirements, it can be seen that the strength indicators in the industry specifications are met, indicating that the use of high-titanium blast furnace slag as wear-resistant floor aggregate is feasible in terms of strength.

[0074] (ii) Wear resistance ratio

[0075] The floor wear-resistant layer mortar (A5) prepared in Example 1 and the reference mortar (the reference mortar is proportioned according to the relevant requirements of "Cement-based Wear-resistant Materials for Concrete Floors JCT906-2002") were molded and cured for 28 days according to GB / T17671-2021 to obtain mortar specimens, with 5 specimens in each group, and the wear resistance ratio of the mortar specimens was measured (the wear resistance test process is shown in Figure 2 ), the results are shown in Table 9.

[0076] Wear resistance ratio is one of the important parameters for evaluating the wear resistance of materials and is calculated according to formula (1):

[0077]

[0078] Where:

[0079] I—wear resistance ratio, %;

[0080] I0—wear resistance value of benchmark mortar;

[0081] I1—The wear resistance value of the floor wear-resistant layer mortar.

[0082] Table 9 Wear resistance ratio of mortar specimens

[0083] Test specimen Wear resistance Wear resistance ratio% Benchmark mortar 0.9 -- Floor wear-resistant mortar (A5) 3.97 441 Industry Standards / 300

[0084] It can be seen from Table 9 that the floor wear-resistant layer mortar (A5) specimen prepared by adding high-titanium blast furnace slag in the present invention meets the wear resistance ratio requirements in the industry specifications, indicating that it is feasible to use high-titanium blast furnace slag as wear-resistant floor aggregate in terms of wear resistance.

[0085] (III) Surface strength

[0086] After the wear resistance test, the mortar specimens (floor wear-resistant layer mortar (A5) specimens) can be used for surface strength determination. Each group of 5 specimens has 6 test points selected for each specimen. The points should avoid the grinding groove and be evenly dispersed on the surface. The spacing should be greater than 15mm. After the steel ball is used to make the points, the indentation diameter is read with a microscope. The steel ball and the reading microscope used in the test meet the requirements of GB231-1984 (see the test process for details). Figure 3 ).

[0087] It was found that the average surface indentation diameter of the floor wear-resistant layer mortar (A5) specimen prepared by adding high-titanium blast furnace slag of the present invention was 2.36 mm, which is smaller than 3.30 mm in the standard. Therefore, it is feasible to use high-titanium blast furnace slag as wear-resistant floor aggregate in terms of surface strength.

[0088] Comparative Example 1

[0089] A5 is the same as Example 1, except that the high-titanium blast furnace slag is replaced with silica sand (mainly composed of silicon dioxide, with a particle size of 10 to 70 mesh) of equal mass.

[0090] Using the method of Effect Example 1, the 28d flexural strength of the mortar was measured to be 14.6 MPa, the compressive strength was 107.8 MPa, the wear resistance ratio was 368%, and the surface strength was 3.02 mm.

[0091] Comparative Example 2

[0092] A5 is the same as Example 1, except that the high-titanium blast furnace slag is replaced with unscreened high-titanium blast furnace slag of equal mass.

[0093] See the actual picture of unscreened high titanium blast furnace slag Figure 4 The particle size is between 4 and 200 mesh, and 70 to 200 mesh accounts for 30%.

[0094] Table 10 Grading table of unscreened high titanium blast furnace slag

[0095] Particle size (mm) >2.36 1.7~2.36 1.18~1.7 0.6~1.18 0.3~0.6 0.21~0.3 <0.21 Screening mesh number 4 mesh 10 mesh 16 mesh 30 mesh 50 mesh 70 mesh 200 mesh Screening percentage (%) 6 8 13 17 12 14 30

[0096] The performance of the floor wear-resistant layer mortar specimens was determined using the same method as above. The results are shown in Table 11.

[0097] Table 11 Performance of floor wear-resistant layer mortar specimens

[0098]

[0099] Comparative Example 3

[0100] The same as A5 of Example 1, except that the particle size of the high titanium blast furnace slag is between 8 and 140 meshes, and the grading ratio is shown in Table 12.

[0101] Table 12 Grading table of high titanium blast furnace slag

[0102] Particle size (mm) 2.36~3.35 1.7~2.36 1.18~1.7 0.6~1.18 0.3~0.6 0.21~0.3 0.1~0.21 Screening mesh number 8 mesh 10 mesh 16 mesh 30 mesh 50 mesh 70 mesh 140 mesh Screening percentage (%) 5 10 25 30 15 10 5

[0103] The performance of the floor wear-resistant layer mortar specimens was determined using the same method as above. The results are shown in Table 13.

[0104] Table 13 Performance of floor wear-resistant layer mortar specimens

[0105]

[0106] Comparative Example 4

[0107] The same as A5 of Example 1, except that the particle size of the high titanium blast furnace slag is between 8 and 70 meshes, and the grading ratio is shown in Table 14.

[0108] Table 14 Grading table of high titanium blast furnace slag

[0109] Particle size (mm) 2.36~3.35 1.7~2.36 1.18~1.7 0.6~1.18 0.3~0.6 0.21~0.3 Mesh 8 mesh 10 mesh 16 mesh 30 mesh 50 mesh 70 mesh Screening percentage (%) 5 10 28 30 15 12

[0110] The performance of the floor wear-resistant layer mortar specimens was determined using the same method as above. The results are shown in Table 15.

[0111] Table 15 Performance of floor wear-resistant layer mortar specimens

[0112]

[0113] Comparative Example 5

[0114] Similar to A5 in Example 1, the particle size of high titanium blast furnace slag is between 10 and 70 meshes, the only difference being the grading ratio. The ratios are shown in Table 16.

[0115] Table 16 Grading table of high titanium blast furnace slag

[0116] Particle size (mm) 1.7~2.36 1.18~1.7 0.6~1.18 0.3~0.6 0.21~0.3 Mesh 10 mesh 16 mesh 30 mesh 50 mesh 70 mesh Screening percentage (%) 10 35 30 17 8

[0117] The performance of the floor wear-resistant layer mortar specimens was determined using the same method as above. The results are shown in Table 17.

[0118] Table 17 Performance of floor wear-resistant layer mortar specimens

[0119]

[0120] Comparative Example 6

[0121] Similar to A5 in Example 1, the particle size of high titanium blast furnace slag is between 10 and 70 meshes, the only difference being the grading ratio. The ratios are shown in Table 18.

[0122] Table 18 Grading table of high titanium blast furnace slag

[0123] Particle size (mm) 1.7~2.36 1.18~1.7 0.6~1.18 0.3~0.6 0.21~0.3 Mesh 10 mesh 16 mesh 30 mesh 50 mesh 70 mesh Screening percentage (%) 8 37 35 15 5

[0124] The performance of the floor wear-resistant layer mortar specimens was determined using the same method as above. The results are shown in Table 19.

[0125] Table 19 Performance of floor wear-resistant layer mortar specimens

[0126]

[0127] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A floor wear-resistant layer mortar based on high-titanium blast furnace slag, characterized in that: Raw materials include cement, silica fume, high-titanium blast furnace slag, water reducer and water; The mass ratio of the cement to the high-titanium blast furnace slag is (35-45):(55-65).

2. The floor wear-resistant layer mortar according to claim 1, characterized in that: The water-cement ratio of the floor wear-resistant layer mortar is 0.20 to 0.28; The dosage of the water reducing agent is 0.06-0.12% of the total mass of cement and high-titanium blast furnace slag.

3. The floor wear-resistant layer mortar according to claim 1, characterized in that: The floor wear-resistant layer mortar includes the following raw materials in parts by mass: 770 parts of cement, 22 parts of silicon powder, 1430 parts of high-titanium blast furnace slag, 221.80 parts of water and 2.64 parts of water reducing agent.

4. The floor wear-resistant layer mortar according to claim 1, characterized in that: The particle size of the high-titanium blast furnace slag is 10-70 meshes.

5. The floor wear-resistant layer mortar according to claim 1, characterized in that: The content of TiO2 in the high-titanium blast furnace slag is 20-28%.

6. A method for preparing a floor wear-resistant layer mortar according to any one of claims 1 to 5, characterized in that: The following steps are involved: The raw materials are mixed evenly to obtain the floor wear-resistant layer mortar.

7. Use of the floor wear-resistant layer mortar according to any one of claims 1 to 5 as a floor material.

Citation Information

Patent Citations

  • High-titanium slag sand reactive powder concrete and preparation method thereof

    CN111348871A

  • Carborundum colored crystal floor mortar containing copper slag and construction method of carborundum colored crystal floor mortar

    CN113372043A